Preparation and Characterisation of Polyurethane Acrylate-Based Titanium Dioxide Pigment for Blue Light-Curable Ink - Chenglong Wang (MDPI AG, 2021)
Herein, a polyurethane acrylate-based TiO2 (PU-TiO2) was fabricated using a two-step method. First, a polyurethane prepolymer was prepared. Second, PU-TiO2 was prepared using amino-modified TiO2 (A-TiO2). The best synthesis process of the polyurethane prepolymer was when the reaction temperature was 80 °C, the reaction time was 3 h and the R-value of the polyurethane acrylate was 2. Next, the influence of the A-TiO2 content on the structure and performance of PU-TiO2 was examined. The analysis of the rheological properties of the PU-TiO2 ink indicated that its viscosity gradually increased as the A-TiO2 content increased. The tensile performance of film improved because of the presence of A-TiO2. The photo-polymerisation and photo-rheological performance indicated that the PU-TiO2 structure changed from a hyperbranched structure with TiO2 as the core to a segmented structure, as the A-TiO2 content was 3%.